2020
DOI: 10.1002/cctc.202001368
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic‐organic Frameworks CoMo‐ZIF‐67: An Efficient and Stable Catalyst for Selective Oxidation of Alkenes

Abstract: Developing catalysts for the selective oxidation of alkenes with environment‐friendly, unique structural characteristics, high economic benefit and better catalytic performance is important. Herein, we employed ZIF‐67 as the sacrificial template to synthesize bimetallic‐organic frameworks CoxMo100‐x‐ZIF nanocages by a facile dissolution‐regrowth strategy. The Co51.8Mo48.2‐ZIF catalyst was tested under various experimental parameters for the selective oxidation of cyclooctene to screen the optimal reaction cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…In addition, the catalytic performance of Co 51.8 Mo 48.2 -ZIF nanocages was still maintained after repeated use for 5 catalytic cycles. [91] CoxMo100-x-ZIF nanocages have excellent catalytic performance, mainly due to the synergistic effect of Co and Mo sites and high specific surface area hollow structure. 20.…”
Section: Co-based Mofsmentioning
confidence: 99%
“…In addition, the catalytic performance of Co 51.8 Mo 48.2 -ZIF nanocages was still maintained after repeated use for 5 catalytic cycles. [91] CoxMo100-x-ZIF nanocages have excellent catalytic performance, mainly due to the synergistic effect of Co and Mo sites and high specific surface area hollow structure. 20.…”
Section: Co-based Mofsmentioning
confidence: 99%
“…Zeolite imidazole frameworks (ZIFs), which assembled from metal ions as centers and organic ligands through coordination reactions, are ideal candidates for hollow structure catalysts with high surface area and specific lattice order. [19] Therefore, ZIFs materials have been widely studied in electrocatalysis, [20][21][22] alkenes epoxidation [23][24][25] and desulfurization. [26][27][28][29] Although a mass of ZIFs-derived catalysts have been reported, researches on ZIFs as templates to prepare hollow dioxygen compounds for CO low-temperature catalytic oxidation are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-Organic Frameworks (MOFs) can be used as catalysts in NTP synergistic catalytic reactions due to their active chemical properties and controllable structure (Zhang et al, 2018;Vakili et al, 2020). MOFs are a new class of porous frameworks formed by the self-assembly reaction of metal ions and organic ligands (Guo Y. et al, 2021). Yaghi's group (Yaghi et al, 1995;Furukawa et al, 2013) reported the successful preparation of MOFs, which aroused great research interest from scholars all over the world, and made MOFs enter a stage of rapid development (Li H.-Y.…”
Section: Introductionmentioning
confidence: 99%
“…W.H. Zou et al (Zou et al, 2021) prepared the new material by adding Mo into the structure of ZIF-67 to form abundant catalytic active centers and hollow structure, which exhibited excellent catalytic performance. The solvothermal synthesis method is simple in operation and easy to control the preparation conditions, and is the most commonly used method for the preparation of MOFs.…”
Section: Introductionmentioning
confidence: 99%